GEOTHERMAL RESERVOIR DEPTH OF SEULAWAH AGAM VOLCANO ESTIMATED FROM 1D MAGNETOTELLURIC - Marwan; Yanis, Muhammad; Zahratunnisa; Idroes, Rinaldi; Nugraha, Gartika; Budi Dharma, Dian; Susilo, Adi; Saputra, Deni; Suriadi (Journal of Applied Engineering Science, 2022)
SeulawahAgam has planned to construct a geothermal power plant with an estimated 275 MW by the government to replace fossil energy. This study used a magnetotelluric (MT) survey to investigate the primary geothermal system, such as heat sources, reservoirs, or faults, which are responsible for regulating the surface manifestation. The regional volcano and fault of the Seulimum segments were traversed by 26 MT stations. The 1D Inversion was conducted toward the overall MT data using the Occam inversion algorithm from IP2Win MT. This Inversion was performed to acquire characteristics of the geothermal system based on resistivity parameters against the depth. The 1D model distribution was combined and converted into pseudo 2D, which could depict the subsurface conditions. Based on the data analysis, the cross-section model revealed that the volcanic sediment layer near the surface had a resistivity of 57–98 Ωm. In the depth of 4–8 km in profile one, and 0.2–2 km, in profile 2, coverage of clay cap rocks was found with impermeable properties, where the resistivity was low (<10 Ωm). Afterward, the reservoir layer was characterized by resistivity ranging from 94 to 188 Ωm located at 1–3 km depth, where this anomaly could be seen across all measuring tracks. Meanwhile, the region beneath the reservoir was estimated to be a heat source with a depth range of 2–5 km, as evidenced by a high resistivity of more than >1000 Ωm. The pseudo-2D results could provide an initial model of SeulawahAgam’s geothermal system.